(untitled) (Journal of Medical & Health Sciences Review, 2025)
Antenatal care services provision is the key element for the reduction in maternal mortality rate neonatal mortality rate and prevention of complications during child birth. The present research has been designed to investigate the different factors that are influencing the ANC utilization process as well as women’s medication intake behavior. The study was carried out in Lahore city, one of the major cities in Punjab and hub for culture in Pakistan. The study aimed to gain information and knowledge on women’s trends and attitudes regarding receiving of maternal health care services and medication intake behavior in Lahore, Punjab, and province of Pakistan. Ten sites were selected in Lahore for data collection through random sampling simple technique i.e. Jinnah Hospital, Sir Ganga Ram Hospital, Fatima Memorial Hospital, Saira Memorial Hospital, Youhanabad Society, Maternity and Child welfare association of Pakistan, Johar Town society, Akhuwat Foundation Pakistan, Kahna Nau and Barki Village. From each selected site 48 respondents were selected randomly; who fulfill the study inclusion criteria i.e. the mothers aged from 15-45 years either pregnant or delivered their last child at least 6 months back. Sample size of (480) was fixed using equal allocation method. A well-structured questionnaire about antenatal care and medication intake was designed for this purpose. Quantitative research technique was applied for data analysis. Descriptive statistics and multiple regression analysis methods were used for data analysis. It was observed that only 14% of respondents were not aware of important ANC services and their major source of obtaining information about maternal care and their medications were Gynecologist. A huge number of respondents assured availability of maternal health care facilities near their residence and only 14% denied its availability. Majority of respondents received 4 or more than 4 visits (42%). Educational level of mothers and fathers, income of the family, knowledge about maternal care, availability of maternal care services, occupation of mothers and fathers, age of respondents and number of children all have positive and significant association with the utilization of maternal care services, whereas, influence of cost of antenatal care services had negative and significant association with the utilization of antenatal care services. Similarly education level of mothers and fathers, age of mothers, income of family, availability of health services like medicines respondents and their husbands occupation have positive and significant impact on women medication intake behavior while cost of medicines and culture have negative and significant influence on women medication intake behavior. Strategies should be designed for enhancing role of media in improving maternal care, improving hygiene and sanitation of health care setting, improving attitude, behavior and level of knowledge of health care staff. In addition, cost of ANC services and medicines should be minimized because huge majority of women do not avail quality health services because of cost.